Communication Ethics In Social Media Among The Millennial Generation - fitria, lale (Universitas Negeri Surabaya, 2024)
The purpose of this article is to provide an overview of the communication ethics of the millennial generation on social media from a Pancasila perspective and according to the role of Pancasila moral values in dealing with technological developments. Advances in technology and science are directly eroding the ethics of using social media, thereby slowly reducing the noble values of Pancasila, which is the life guide and ideology of the unitary state of the Republic of Indonesia. In the era of the millennial generation, the use of social media is often misused. The reason is, the millennial generation tends to be susceptible to content spread on social media without filtering it critically. They truly believe that the content is fact, so they try to defend it with their stance. Socialization, regulatory enforcement, and social media literacy are some of the external ways in which this problem can be solved. Another internal way is to instill in the millennial generation various values and standards of life based on Pancasila and encourage the millennial generation to be involved in various positive productive activities on social media.